Anxiety levels in employees and students in psychiatric nursing - Bole, Urban (Obzornik zdravstvene nege, 2016)
Introduction: Several research finding indicate that nursing care professionals are often faced with situations which may lead to anxiety. The aim of the present research was to determine the prevalence and typical signs of anxiety among nursing employees and nursing students in psychiatric settings. Methods: The Burns Anxiety Inventory was used as an assessment tool to measure anxiety. The research sample consisted of 242 participants. The data collected were processed by the descriptive statistics, Levene's test, the ANOVA statistical test, the Welch's t-test, and the post hoc analysis. Pearson's correlation coefficient was used to measure the strength of the association between the variables. Results: The results of the current study show that nearly half of the participants experience anxiety, but the differences were noted as regards their anxiety thoughts (p = 0.039). Anxiety feelings are more prevalent in female students (p = 0.046). Habitual smokers (p = 0.030) and casual smokers (p = 0.020) are more likely to develop anxious feelings and physical signs of anxiety. The anxiety signs are also more pronounced in the respondents with self-assessed lower economic status (p = 0.001) and poor self-rated health (p = 0.0001). Discussion and conclusion: The professionals and students in psychiatric nursing often encounter situations conducive to the development of anxiety. Further studies on the current topic are therefore recommended to design adequate educational programmes to timely recognise anxiety symptoms and to implement mutual and self-help measure.
Keywords: burnout; health care; izgorelost; medicinske sestre; nurses; stres; stress; zdravstvo